Efektivitas Penggunaan Media Sosial TikTok Sebagai Platform Pemasaran Digital Produk Olahan Buah Frutivez (@hellofrutivez) - Azhari, Sartika; Ardiansah, Irfan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2022)
Frutivez is a healthy snack product derived from fruit-puree processed using dehydration technology which is presented in strips. Along with the conditions of the COVID-19 pandemic in Indonesia, people tend to change their lives to be healthier, so now Frutivez has greater opportunities to introduce its products to consumers. Frutivez utilizes digital marketing as its online marketing platform, especially on TikTok. TikTok users in Indonesia are dominated by millennials. Frutivez utilizes TikTok as a marketing platform by presenting video content that allows TikTok audiences to find out more about Frutivez products on TikTok account @hellofrutivez. However, most trends on TikTok’s social media continue to change every day, so the companies must be ready and responsive to change and conduct evaluations by achieving marketing goals. In this study, the use of TikTok social media on the TikTok @hellofrutivez account uses quantitative descriptive analysis. The first model analysis used is the Three Layers of Social Media. The second model analysis is the SWOT analysis. The results of this study indicate the measurement results of video content that show a positive response to each content and generate the highest engagement on video content of the banana strips making process. The results of the SWOT analysis on the TikTok @hellofrutivez account provide several strategies that can be used to develop Frutivez online marketing on TikTok social media.